Assessment of long-term risks of secondary cancer in paediatric patients with brain tumours after boron neutron capture therapy. (7th August 2019) - Zhang, Xinxin; Geng, Changran; Tang, Xiaobin; Bortolussi, Silva; Shu, Diyun; Gong, Chunhui; Han, Yang; Wu, Shaojuan
Abstract: This study firstly explored the risks of secondary cancer in healthy organs of Chinese paediatric patients with brain tumours after boron neutron capture therapy (BNCT). Three neutron beam irradiation geometries (i.e. right lateral, top to bottom, posterior to anterior) were adopted in treating patients with brain tumours under the clinical environment of BNCT. The concerned organs in this study were those with high cancer morbidity in China (e.g. lung, liver and stomach). The equivalent doses for these organs were calculated using Monte Carlo and anthropomorphic paediatric phantoms with Chinese physiological features. The risk of secondary cancer, characterised by the lifetime attributable risk (LAR) factor given in the BEIR VII report, was compared among the three irradiation geometries. The results showed that the LAR was lower with the PA irradiation geometry than with the two other irradiation geometries when the 2 cm diameter tumour was at a depth of 6 cm on the right side of the brain. Under the PA irradiation geometry, the LAR in the organs increased with increasing tumour volume and depth because of the long irradiation time. As the patients aged from 10–15 years old, the LAR decreased, which was related to the increased patient height and shortened life expectancy. Female patients had a relatively higher risk of secondary cancer than male patients in this study, which could be due to the thinner body thickness and the weaker protective effect on the internal organs of the female patients. In conclusion, the risks of secondary cancer in organs were related to irradiation geometries, gender, and age, indicating that the risk of secondary cancer is a personalised parameter that needs to be evaluated before administering BNCT, especially in patients with large or deep tumours.